Timeliness of annual report releases in relation to the direction and magnitude of earnings and share price evaluation : the case of Malaysia - Cheng, Fan Fah * (Sunway University College, 2006)
This paper examines the relationship between the timing of earnings announcement and the direction and magnitude of earnings for more than 2482 firm-years in the Bursa Malaysia. The results confirm that CEOs time their earnings announcement based on the direction and magnitude of the unexpected earnings. CEOs announce earnings early for positive unexpected earnings, and delay the announcement for negative unexpected earnings. The market reacts to the timing of the announcement accordingly. These findings are relevant and useful to judge company performance by observing the announcement date of the company, especially those that perform less than satisfactorily in anticipation of bad news release from these firms.